KERAGAAN FENOTIFIK BEBERAPA GENOTIPE MENTIMUN (Cucumis sativus L.) - Gungun Wiguna (MEDIAGRO, 2014)
The aims of this research to evaluate and get a description of the important properties of some genotypes of cucumber to be used as a material in further breeding programs. The study was conducted at the experimental garden Indonesian Vegetables Research Institute, Lembang, 1,250 meters above sea level from June to August 2014. The research material using five genotypes of cucumber seed germplasm collections along with seven genotypes its segregan and 6 commercial varieties. Research using randomized block design (RAK). The results showed genotype LV 2904-2, LV2276-3, LV 2276-4, LV2902-1 and commercial 1 could potentially be developed further because it has the character according to the tastes of consumers. Genotypes with high yield potential generated by LV 2904-1, LV2276-3, LV 2276-6, LV2276-7 and commercial 1.   Keywords: Cucumber, genotype, phenotypic.